2016
DOI: 10.7896/j.1532
|View full text |Cite
|
Sign up to set email alerts
|

Participation of disadvantaged groups and governance in the LEADER and PRODER programmes in Andalucía, Spain

Abstract: The involvement of disadvantaged groups in European Union neo-endogenous rural development programmes, such as the LEADER programme, must be a high priority. In this paper we study the profi les of the benefi ciaries of LEADER and PRODER, the main Spanish example of mainstreaming the LEADER method, in the NUTS 2 region of Andalucía, Spain in the period [2002][2003][2004][2005][2006][2007][2008], and of the decision makers in the Local Action Groups (LAGs). Using quantitative information provided by the regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Structured interviews with LAGs managers were used as a primary method for collecting data. The method is often used in LEADER related research [10,11]. The interview consisted in 12 questions divided in four sections (Table 1) and was designed after consultations with LAGs experts (researchers, LAG managers and consultants).…”
Section: Methodsmentioning
confidence: 99%
“…Structured interviews with LAGs managers were used as a primary method for collecting data. The method is often used in LEADER related research [10,11]. The interview consisted in 12 questions divided in four sections (Table 1) and was designed after consultations with LAGs experts (researchers, LAG managers and consultants).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, due to various factors including $self-selection% of participants, and the lower visibility and more fragmented geographies of minorities in rural areas, it cannot be assumed that more democratic governance arizes from increased participation without greater scrutiny (Muller, Sutter, Wohlgemuth 2020). Navarro, Cejudo, and Maroto (2016) adduce a long list of authors who found that the LEADER and/or endogenous development approach can reinforce existing power structures and marginalize the poor.…”
Section: Critiques Of Democratic Participation and Autonomy In Leadermentioning
confidence: 99%
“…However, the program's territory is one of the areas with less activity compared to other more populated and dynamic rural surroundings. LEADER and PRODER Programmes have tended to penalise disadvantaged rural zones that are facing problems of depopulation and social and economic decline [52]. During the last few years, only small rural tourism initiatives or services aimed at improving internet access have been launched.…”
Section: Case Studies Overviewmentioning
confidence: 99%